Acoustic trap-and-release for rapid assessment of cell motility. Issue 21 (10th April 2019) - Kim, Minji; Huff, Emma; Bottier, Mathieu; Dutcher, Susan K.; Bayly, Philip V.; Meacham, J. Mark
Abstract : Acoustic confinement and subsequent release enable aggregate, highly sensitive measurement of swimming effectiveness for populations of dispersing cells. Abstract : Functional cilia and flagella are crucial to the propulsion of physiological fluids, motile cells, and microorganisms. Motility assessment of individual cells allows discrimination of normal from dysfunctional behavior, but cell-scale analysis of individual trajectories to represent a population is laborious and impractical for clinical, industrial, and even research applications. We introduce an assay that quantifies swimming capability as a function of the variation in polar moment of inertia of cells released from an acoustic trap. Acoustic confinement eliminates the need to trace discrete trajectories and enables automated analysis of hundreds of cells in minutes. The approach closely approximates the average speed estimated from the mean squared displacement of individual cells for wild-type Chlamydomonas reinhardtii and two mutants ( ida3 and oda5 ) that display aberrant swimming behaviors. Large-population acoustic trap-and-release rapidly differentiates these cell types based on intrinsic motility, which provides a highly sensitive and efficient alternative to conventional particle tracing.